Investigation in to the Positional Running Demands of Elite Gaelic Football Players: How Competition Data Can Inform Training Practice. Issue 7 (July 2020) - McGahan, Jason; Burns, Con; Lacey, Seán; Gabbett, Tim; O'Neil, Cian
Abstract : ABSTRACT: McGahan, J, Burns, C, Lacey, S, Gabbett, T, and Neill, CO. Investigation in to the positional running demands of elite Gaelic football players: How competition data can inform training practice. J Strength Cond Res 34(7): 2040–2047, 2020—This study investigated the positional running demands of elite Gaelic football players during match play and compared these demands with typical training activities used to prepare players for competition. Global positioning system (GPS) data were obtained from 30 elite Gaelic football players (26.9 ± 3.5 years, 182.8 ± 6.1 cm, 84.6 ± 8.1 kg) across a full season (13 competitive games and 78 training sessions). Only players who completed the full match and respective training sessions were included ( n = 107 match files and n = 1, 603 training files). Data were collected using 4-Hz GPS units (VX Sport, Lower Hutt, New Zealand). Mean high speed (≥17 km·h −1 ; m·min −1 ), mean speed (m·min −1 ), percentage at high speed (%), and mean sprint efforts (≥17 km·h −1 ; no.·min −1 ) were recorded. Running variables were analyzed across the 5 outfield positional lines in Gaelic football (full back [FB], half back [HB], midfield [MF], half forward, and full forward [FF]). For mean high-speed running and mean speed, significant relationships (range r = 0.811–0.964 and r = 0.792–0.998, respectively) were found between competition and game-based training for players in the FB, HB, MF, and FF lines ( p ⩽ 0.05). Analyses of mean sprint efforts and percentage at high speed found positive correlations between competition and training activities across each of the positional lines. Appropriately designed training activities can ensure that the position-specific demands of elite Gaelic football competition are met using a game-based training approach. Collectively, these findings demonstrate the value of and provide support for the use of a game-based training approach as a method of preparing players for the physical demands of competition in elite Gaelic football.